Kinetic Modeling of the Photocatalytic Degradation of Chlorinated Aromatic Volatile Organic Compounds: Mass Transfer Enhancement - N’Zanon Aly Koné; Amine Aymen Assadi; Nacer Belkessa; Lotfi Khezami; Sandotin Lassina Coulibaly; Youcef Serhane; Walid Elfalleh; Lacina Coulibaly; Abdelkrim Bouzaza; Abdeltif Amrane (Applied Sciences, 2024)
Chlorobenzene (CB) and Chloronaphthalene (CN) emissions from cement plant operations pose significant environmental risks. This study investigates the mass transfer effects of chlorinated aromatic Volatile Organic Compounds (VOCs), specifically CB and CN, in the gas phase of a continuous-tangential-flow annular photocatalytic reactor. The experiments involved introducing CB and CN into the reactor, and the degradation kinetics were analyzed using the Langmuir–Hinshelwood (L-H) model. The L-H model was applied to assess the impact of the flow rate, concentration, and relative humidity (% RH) on the degradation rate (DR). The results indicate that both the experimental and simulated degradation rates improved with increased flow rates (1 to 9 m3·h−1) and inlet concentrations (30 to 216 mg·m−3). This enhancement of the DR correlates with the availability of active OH* species on the TiO2 surface. The L-H model emphasizes the role of H2O molecules in VOC removal kinetics. The degradation rates increased with a rising water content (5 to 55%), but adverse effects on VOC conversion were observed beyond a 55% RH. This study reveals a mass transfer effect, with internal diffusional limitations in the TiO2 pores under operational conditions. The kinetics were predominantly controlled by chemical kinetics and catalyst pore availability. Furthermore, this study demonstrates a higher CB degradation than CN in the reactor and experimental conditions. For a concentration of 1.328 mM·m−3, the CB DR ranged from 0.70 to 2.84 µM·m2·s−1, as the flow rate varied from 1 to 9 m3·h−1. The CN DR varied from 0.60 to 2.20 µM·m2·s−1 within the same flow rate range.